2006
DOI: 10.1177/0021998305055276
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Contribution of Various Wood Fibers to Composite Materials

Abstract: Wood pulp fibers can serve as useful reinforcement of plastics for increased stiffness. To assess the potential of various wood fibers as reinforcement, a method has been developed to determine the contribution of the fibers to the elastic properties of the composite. A micromechanical composite model and classical laminate mechanics are used to relate the elastic properties of the fibers to the elastic properties of the composite. A large variety of composites made of various wood pulp fibers in an epoxy viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 47 publications
6
76
0
1
Order By: Relevance
“…For structural and semi structural applications, the most relevant properties are probably stiffness and dimensional stability [23]. Lopez et al [2] found a 1.09 ratio between the Young modulus of 30% glass fiber (GF)-polypropylene and 50% stone groundwood mechanical pulp -polypropylene composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For structural and semi structural applications, the most relevant properties are probably stiffness and dimensional stability [23]. Lopez et al [2] found a 1.09 ratio between the Young modulus of 30% glass fiber (GF)-polypropylene and 50% stone groundwood mechanical pulp -polypropylene composites.…”
Section: Introductionmentioning
confidence: 99%
“…In order to predict the elastic properties of the composite materials it is necessary to know the intrinsic Young's modulus of the fibers, defined as the average slope in the stress-strain curve in the strain interval from 0 to 0.3% [23]. Unfortunately, due to their characteristic morphology, the experimental evaluation of the Young's moduli of ONF is costly and difficult, and sometimes impossible.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of hemicelluloses to fiber strength has been widely discussed and is not entirely clear (Spiegelberg 1966;Schonberg et al 2001). The effect of lignin on tensile strength and tensile stiffness of paper sheets has been reported (Risen et al 2004;Neagu et al 2006). The correlation between the cellulose degradation and fiber strength has also been discussed (Gurnagul et al 1992;Joutsimo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage error between the predicted values from the experimental samples for tensile index, tear index, double fold and burst index, were used as the performance criteria of the ANN models. The mean absolute error (MAE), the mean absolute percentage error (MAPE), the root mean square error (RMSE), and correlation coefficient (R²) were used to evaluate the prediction performance of the models [11]. The models yielding the best results for tensile index tear index, burst index and double fold were considered as the prediction models.…”
Section: Mlr and Ann Modeling Methodsmentioning
confidence: 99%
“…Various research groups have also made efforts to explore the relationship between chemical and physical properties of the pulp fiber and their inherent paper making strength properties. MLR has been used to explore possibility of correlation between morphological features and the strength parameters by various researchers [3][4][5][6][7][8][9][10][11]. Similarly possibility of application of ANN in the paper industry has also been reported in various articles [12][13][14][15][16][17][18] to use neural network based model for prediction of paper properties based on factors related to the most important refining effects, such as the fiber and pulp average length, width and fines content.…”
Section: Introductionmentioning
confidence: 99%